A Comparative Prospective Cohort Study Comparing Physical Exam to Ultrasound for Identifying the Cricoid Cartilage. Issue 9 (September 2017) - Williams, P; Umranikar, A
Applying cricoid pressure is a common practice when intubating patients thought to be at risk of pulmonary aspiration. Recently, the perceived benefits of applying cricoid pressure have been questioned. Prior research has shown that cricoid pressure is applied incorrectly and that palpation of adjacent anatomy of the cricothyroid membrane is also inaccurate. We compared physical palpation to ultrasound for identifying the location of the cricoid cartilage using a total of 50 assessments. The median distance to target was 10mm. We concluded that palpation is an inaccurate method to locate the cricoid cartilage in the studied population.